Rekognisi Keadilan Restoratif sebagai Mekanisme Penyelesaian Pidana Adat Masyarakat Baduy dalam Pluralisme Hukum Nasional - Putri, Sovi Ayudia; Noviyanti, Fitri; Romdoni, Muhamad (Fakultas Hukum Universitas Primagraha, 2025)
Legal pluralism in Indonesia recognizes customary law as part of the national legal system, although its acknowledgment remains limited. The Baduy community applies restorative justice through the Silih Hampura principle, emphasizing the restoration of social relationships. This approach differs from the retributive nature of the national criminal justice system. Challenges such as differences in legal paradigms, lack of understanding among law enforcement officers, and the risk of criminalization hinder the recognition of customary mechanisms. This study aims to examine the recognition of restorative justice as a mechanism for resolving customary criminal cases within the Baduy community in the framework of national legal pluralism. Using normative legal research methods and a descriptive qualitative approach, this study highlights the application of Silih Hampura, which focuses on restoring social relations between offenders, victims, and the community. The findings indicate that the Baduy’s customary criminal settlements align with restorative justice principles, although challenges persist. Integrating the Baduy's restorative justice into the national legal system strengthens the protection of indigenous rights, as reflected in Law No. 39 of 1999 on Human Rights and Law No. 6 of 2014 on Villages. Stronger recognition is needed to preserve cultural diversity and promote social justice in Indonesia.